2019
DOI: 10.1055/a-0951-0017
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from Strenuous Downhill Running in Young and Older Physically Active Adults

Abstract: There is a well-conceived notion that rate of recovery from strenuous exercise gets slower with age. However, it is unclear whether older adults who exercise habitually demonstrate slower rates of recovery. We determined whether older adults who are physically active demonstrate slower rates of recovery from unaccustomed strenuous exercise compared with younger peers. Healthy young sedentary (n=10, 28±2 years), young endurance-trained (n=15, 27±2 years), and older endurance-trained (n=14, 58±2 years) men and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 36 publications
(66 reference statements)
2
16
1
Order By: Relevance
“…Many studies have investigated adaptations to DR in adult populations, but only a limited number have included adolescents, pre-pubescent children and older populations. Some studies did not report differences in indirect markers of muscle damage between pre-pubescent children and adults [191], or between young and older trained triathletes [180] after DR. Other studies reported trends towards higher levels of indirect markers of muscle damage (neutrophil counts, plasma CK and DOMS) in young men compared to older men after DR [8,142] but with comparable recovery kinetics [8]. Additional studies are required to better understand the effect of maturation and/or age on the physiological responses to DR.…”
Section: Other Factors Potentially Influencing Muscle Damage Followinmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have investigated adaptations to DR in adult populations, but only a limited number have included adolescents, pre-pubescent children and older populations. Some studies did not report differences in indirect markers of muscle damage between pre-pubescent children and adults [191], or between young and older trained triathletes [180] after DR. Other studies reported trends towards higher levels of indirect markers of muscle damage (neutrophil counts, plasma CK and DOMS) in young men compared to older men after DR [8,142] but with comparable recovery kinetics [8]. Additional studies are required to better understand the effect of maturation and/or age on the physiological responses to DR.…”
Section: Other Factors Potentially Influencing Muscle Damage Followinmentioning
confidence: 99%
“…Thus, the DR modality has often been used for different purposes including: (1) studying the recovery kinetics of physical performance following muscle damage (e.g. [7][8][9]); (2) testing the reliability and validity of varied techniques to assess EIMD (e.g. [6,10]); (3) studying the effects of strenuous exercise on physiological adaptations and/or alterations (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, changes in objective outcomes, including range of motion, markers of muscle damage such as levels of circulating muscle proteins, and performance tests did not differ between younger (27 ± 2) and older (58 ± 2) trained adults following a 45-min downhill run. That study ( Hayashi et al, 2019 ), however, did not assess inflammatory markers or examine changes in muscle integrity (for example via magnetic resonance imaging; MRI) in order to evaluate differences in the effect of exercise-induced muscle damage (EIMD) between age groups at the muscle fibers level.…”
Section: Introductionmentioning
confidence: 99%
“… 3 For example, after downhill running exercises, muscle damage markers such as the knee extension strength and the muscle soreness have been found to increase and remain elevated for days. 4 , 5 Anecdotally, this is usually reflected by a longer-than-normal recovery time following a long-distance race that contains a downhill running portion, when compared to the level or uphill running with the same running distance or intensity.…”
Section: Introductionmentioning
confidence: 99%